2013
DOI: 10.1080/08841233.2013.775211
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Curriculum and MSW Students' Attitudes about Race and Diversity

Abstract: Methods of incorporating culturally competent practice and social justice curricula often are addressed in a required course or across courses using an infusion model. This research explored multicultural curricula and MSW students' attitudes about race and diversity. Data were collected from 297 MSW students enrolled at two universities. Multivariate analysis of variance revealed significant differences between students in programs with required multicultural coursework and those utilizing an infusion model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
1
8
1
Order By: Relevance
“…For example, content to be integrated is often (a) positioned as "in competition" for space in an already crowded course or course sequence, (b) delivered in a way that may seem supplemental and non-essential to the "core" objectives of the course or the program, (c) treated with insufficient depth and/or skipped in cases of insufficient time in non-dedicated courses, and(d) alienated as yet another burden on faculty and student time should a dedicated course be developed (Hooyman, 2006). Social work education faces the challenge of selecting a means for integrating social justice content into curricula despite insufficient empirical exploration of the associations between various training models, sustained practice behavior, and practice outcomes with clients in the area of multicultural or justice-oriented education (Yaffe, 2013;Brach and Fraser, 2000).Recent studies have suggested that very little variance in student attitudes toward social justice is explained by whether a student participated in a required multicultural or social justice oriented course (Osteen, Vanidestine and Sharpe, 2013). Similarly, recent research did not detect a relationship between participation in such requirements and subsequent social justice actions (e.g., challenging derogatory comments; Pittman, 2009).…”
Section: Approaches To Curricular Reformmentioning
confidence: 99%
“…For example, content to be integrated is often (a) positioned as "in competition" for space in an already crowded course or course sequence, (b) delivered in a way that may seem supplemental and non-essential to the "core" objectives of the course or the program, (c) treated with insufficient depth and/or skipped in cases of insufficient time in non-dedicated courses, and(d) alienated as yet another burden on faculty and student time should a dedicated course be developed (Hooyman, 2006). Social work education faces the challenge of selecting a means for integrating social justice content into curricula despite insufficient empirical exploration of the associations between various training models, sustained practice behavior, and practice outcomes with clients in the area of multicultural or justice-oriented education (Yaffe, 2013;Brach and Fraser, 2000).Recent studies have suggested that very little variance in student attitudes toward social justice is explained by whether a student participated in a required multicultural or social justice oriented course (Osteen, Vanidestine and Sharpe, 2013). Similarly, recent research did not detect a relationship between participation in such requirements and subsequent social justice actions (e.g., challenging derogatory comments; Pittman, 2009).…”
Section: Approaches To Curricular Reformmentioning
confidence: 99%
“…To my knowledge, no study except Osteen et al. () has empirically examined the ethnic and racial attitudes of social work students. However, their study is limited by a small number of explanatory variables.…”
Section: Correlates Of Ethnic and Racial Diversity Attitudes In The Lmentioning
confidence: 99%
“…First, this paper is the first to explore the influence of multicultural education on social work students' attitudes toward female SEA marriage migrants in more developed Asian countries. Osteen, Vanidestine, and Sharpe () investigated the impact of multicultural education on Master of Social Work (MSW) students' attitudes toward African Americans. Because of racial history in the United States (US), their findings are not readily applicable to Asian countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations